1991
DOI: 10.1002/ajim.4700200311
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of pulmonary function among workers exposed to multimetals in the glass bangle industry

Abstract: Spirometric lung functions were evaluated in 220 asymptomatic glass bangle workers exposed to the salts of various heavy metals, such as arsenic, lead, zinc, copper, manganese, cobalt, cadmium, and selenium, which are used as coloring agents in the manufacture of glass bangles. The mean values of various spirometric variables (viz. FVC, FEV1, IMBC, and PEFR) were within normal range (more than 80% of the predicted values) in both smoking and nonsmoking glass bangle workers and did not reveal any significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Moreover, O 3 is well known to have deleterious effects on materials, human health and plants (PORG, 1997). Indeed, O 3 is responsible for damages on polymeric materials such as rubbers, but also on textiles, dyes, surface coatings, metals and buildings materials (Lee et al, 1996;Massey, 1999;Ahmad et al, 2000;Almeida et al, 2000;Boyce et al, 2001) and causes deleterious impacts to human health, including lung inflammation, reduction in lung function, respiratory diseases, and mortality (Rastogi et al, 1991;Uysal and Schapira, 2003;Bell et al, 2005;Ito et al, 2005;Levy et al, 2005;Targer et al, 2005;Hazucha and Lefohn, 2007). On vegetation, O 3 slows-down the stomatal closing, decreases the photosynthetic capacity and alters plant biomass and leaf area, although these effects depend on species, canopy structure and age of tissues (Paoletti, 2005;Paoletti and Grulke, 2005;Ainsworth, 2008;Wittig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, O 3 is well known to have deleterious effects on materials, human health and plants (PORG, 1997). Indeed, O 3 is responsible for damages on polymeric materials such as rubbers, but also on textiles, dyes, surface coatings, metals and buildings materials (Lee et al, 1996;Massey, 1999;Ahmad et al, 2000;Almeida et al, 2000;Boyce et al, 2001) and causes deleterious impacts to human health, including lung inflammation, reduction in lung function, respiratory diseases, and mortality (Rastogi et al, 1991;Uysal and Schapira, 2003;Bell et al, 2005;Ito et al, 2005;Levy et al, 2005;Targer et al, 2005;Hazucha and Lefohn, 2007). On vegetation, O 3 slows-down the stomatal closing, decreases the photosynthetic capacity and alters plant biomass and leaf area, although these effects depend on species, canopy structure and age of tissues (Paoletti, 2005;Paoletti and Grulke, 2005;Ainsworth, 2008;Wittig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…24 Exposure to ozone with other heavy metals may result into respiratory failures. 25,26 Hence long term exposure to PM, harmful compounds and heavy metals present in air can be the reason to increasing incidence of asthma, emphysema, and even lung cancer. 27,28 The study observed one or the other symptoms and signs of upper and lower respiratory problems and eye irritation among all the study participants and proposes the utilization of appropriate respiratory defensive gear among street peddlers in Lucknow, India.…”
Section: Resultsmentioning
confidence: 99%
“…lead, copper, zinc, selenium, manganese) [4,5]. Workers from a wide range of industries are exposed daily to metals, from battery factories to lead and cadmium [6], glass industry to selenium [7,8], welders to chromium and nickel [7,9], ceramic workers to manganese [10] and jewellers to silver [7]. Generally, reference values are established in a representative sample of an unexposed population where the upper and lower limits of metal levels are determined statistically based on the distribution of the levels measured.…”
Section: Introductionmentioning
confidence: 99%